Dietary Protein Intake Associations with Insulin Resistance, BMI, Body Composition and Other Metabolic Markers in Subjects with Prediabetes and Type 2 Diabetes Mellitus (P08-020-19). (24th October 2019) - Akhavan, Neda; Johnson, Sarah; Pourafshar, Shirin; Foley, Elizabeth; George, Kelli; Navaei, Negin; Munoz, Joseph; Siebert, Shalom; Hickner, Robert; Levenson, Cathy; Panton, Lynn; Daggy, Bruce; et al.
Abstract: Objectives: The incidence of prediabetes and type 2 diabetes mellitus (T2DM) continues to increase and many individuals are not aware of having early stages of the disease until symptoms develop. Much focus has been on carbohydrate consumption for this population, with no established recommendations for protein intake and source. Therefore, the objective of this study was to examine the relationship between protein intake (amount and source) on glycemic control, and indices of cardiovascular health in individuals with prediabetes and T2DM. Methods: Sixty-two overweight and obese men and women with prediabetes or T2DM, between the ages of 45–75 years participated in this study. Participants were stratified based on their protein intake: below (<0.8 g/kg body weight (bw); n  = 17), meeting (0.8–1.0 g/kg bw; n  = 22), and above (≥1.0 g/kg bw; n  = 23) recommended levels. Measurements included blood biomarkers (lipid panel and glycemic control), anthropometric parameters, food records, and body composition, which were assessed for each group using one-way ANOVA and Pearson correlation coefficient for overall associations. Significance was accepted at (P ≤ 0.05). Results: Body mass index (BMI), hip circumference (HC) and waist circumference (WC) were significantly higher in participants who consumed below recommended levels compared to above (35.1 ± 1.3 vs. 28.3 ± 0.9 kg/m 2 ; 118.7 ± 3.2 vs. 105.2 ± 1.8 cm; 109.1 ± 2. vs. 96.8 ± 2.5 cm, respectively). Fat-to-lean mass (FM/LM) ratio was significantly lower in participants who consumed above recommended when compared to below and recommended levels (0.63 ± 0.03; 0.81 ± 0.04; 0.78 ± 0.07). Insulin resistance tended to be lower (3.53 ± 0.55 vs 5.19 ± 0.94; P  = 0.09) in the above recommended group compared to below. Higher animal-to-plant protein ratios were significantly associated with higher insulin secretion (r = 0.259). Higher animal protein was associated with significantly lower triglyceride concentrations (r = 0.263). Conclusions: These findings suggest that consumption of ≥1.0 g/kg bw protein was associated with lowered insulin resistance, in addition to lower BMI, HC, WC, and FM, without adverse effects on lipid profiles in this population. Additionally, increased animal protein may be associated with better outcomes for this population. Funding Sources: There are no funding sources to disclose for this study.